Simulation Models of Production Plants as a Tool for Implementation of the Digital Twin Concept into Production - Sujová, Erika; Vysloužilová, Daniela; Čierna, Helena; Bambura, Roman (Manufacturing Technology Journal, 2020)
The aim of the paper is to introduce the digital twin concept as part of the Industry 4.0 strategy. In the form of a case study, the procedure and outputs of the simulation of a specific production plant to-gether with its intermediate storage and output for the next plant are presented. In the research part is presented a simulation model of production lines and intermediate stock with material flow represen-tation. At the beginning of the research the analysis of production and logistics processes was carried out. The next part describes the programming methods used to record and redirect material flows between individual lines and stock. The simulation method using simulated production line models enables the digitization of dynamic production processes in enterprises. We expect that in the coming years there will be an increase in demand for the creation of simulation models of production systems in modern manufacturing companies that will try to implement the Industry 4.0 strategy and thus in-crease their competitiveness.
Keywords: Method of Simulation; Digital Twin; Production Plant; Material Flow; Industry 4.0